Navigating Economic Uncertainty: Sectoral Investment Resilience During the COVID-19 Pandemic - Karna, Poonam Kumari Labh (Lembaga Yasin AlSys, 2025)
Global markets have been severely impacted by the COVID-19 epidemic, which has increased economic uncertainty and changed sectoral performance. This study looks at the sectors that fared well throughout the crisis and investigates the wider economic effects of uncertainty brought on by the epidemic. We evaluate the degree of economic uncertainty and its macroeconomic impacts using real-time indicators, such as stock market volatility, news-based uncertainty metrics, and company expectation surveys. According to our research, the pandemic's uncertainty shock is similar to past crises like the Great Depression and the financial crisis of 2008. Additionally, we project a significant drop in the US real GDP, with increased uncertainty accounting for about half of the reduction. These findings highlight the value of forward-looking analyses in assessing economic resilience and offer insightful information for maximising sectoral investment plans in times of international emergency.